2020
DOI: 10.1111/jth.15043
|View full text |Cite
|
Sign up to set email alerts
|

In vitro hypercoagulability and ongoing in vivo activation of coagulation and fibrinolysis in COVID‐19 patients on anticoagulation

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
167
0
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(194 citation statements)
references
References 29 publications
15
167
0
12
Order By: Relevance
“…We confirm and extend published findings on hemostatic alterations in COVID‐19 and compare hemostatic profiles between patients stratified according to level of care and according to level of respiratory support. Previous studies were either small or assessed a limited number of hemostatic tests, but in aggregate these studies are in line with our findings on changes in the VWF/ADAMTS13 axis, 18,30‐33 in vivo and ex vivo activation of coagulation, 18,19,25,34‐36 and in vivo and ex vivo fibrinolytic status 18‐20,26 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We confirm and extend published findings on hemostatic alterations in COVID‐19 and compare hemostatic profiles between patients stratified according to level of care and according to level of respiratory support. Previous studies were either small or assessed a limited number of hemostatic tests, but in aggregate these studies are in line with our findings on changes in the VWF/ADAMTS13 axis, 18,30‐33 in vivo and ex vivo activation of coagulation, 18,19,25,34‐36 and in vivo and ex vivo fibrinolytic status 18‐20,26 …”
Section: Discussionsupporting
confidence: 90%
“…We first assessed disease severity according to level of care and found, in line with existing literature, 18,19 that patients receiving a higher level of care had increased plasma levels of markers of in vivo activation of coagulation and fibrinolysis. Ex vivo thrombin generation was higher compared to controls and similar in patients in general wards and patients in higher levels of care, despite significantly higher doses of LMWH in patients in higher levels of care, confirming our previous findings that current anticoagulant strategies might not be sufficient 18 and suggesting that patients with COVID‐19 are profoundly hypercoagulable before administration of anticoagulants. However, as bleeding complications have also been associated with (severe) COVID‐19, 37 increasing doses of anticoagulant therapy is not without risks, and further research on optimal anticoagulant strategies are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Although our study is specific for TTP identification/exclusion, findings may also have relevance to other situations in which rapid ADAMTS13 testing is desired. We would be foolish, for example to ignore in the COVID‐19 era, recent reports of reduced ADAMTS13 in patients with severe disease, 25‐27 and the likely preference for rapid testing in that setting. Also, clinicians may be faced with critically ill patients with TMA with mild‐moderate reductions in ADAMTS13 activity (eg, patients with pre‐eclampsia, which can be very difficult to distinguish from TTP clinically).…”
Section: Resultsmentioning
confidence: 99%
“…Escher et al [66, 68] reported elevated vWF antigen and function, together with increased FVIII clotting activity in COVID-19 patients, likely reflecting the combined effect of the greater release of Weibel-Palade bodies from endothelial cells and the acute-phase reaction that raises the FVIII level. ADAMTS13 activity is mild-to-moderately reduced in COVID-19 patients [68-70].…”
Section: Endothelium Von Willebrand Factor and Abo Blood Groupmentioning
confidence: 99%